Qualitative Study on Rethinking Liability for Artificial Intelligence Systems Under the Nigerian Jurisprudence and Islamic Legal Ethics View (Federal University Gusau Faculty of Education Journal, 2025)
The rapid integration of Artificial Intelligence (AI) into decision-making processes, from financial services to law enforcement, presents complex challenges regarding accountability and liability. As AI systems increasingly operate with a degree of autonomy, determining who should bear responsibility for harm or error becomes a pressing legal and ethical concern. This paper explores these challenges within the context of Nigerian jurisprudence and Islamic legal ethics, guided by the principles of Maqasid al-Shariah. It examines how conventional legal concepts of human intent and negligence interact with the unique characteristics of algorithmic decision-making, where outcomes may arise from opaque or self-learning processes beyond direct human control. Nigerian law, traditionally rooted in human-centric liability, faces significant gaps in addressing the accountability of autonomous systems. Within this gap, Islamic ethical principles such as Amanah (trust) and Maslahah (public interest) provide a moral framework emphasizing justice, transparency, and societal welfare. The paper proposes a hybrid accountability model that combines statutory responsibility with ethical stewardship, ensuring that innovation aligns with human values and divine justice. However, integrating these legal and ethical perspectives, Nigeria can develop a contextually grounded framework for algorithmic justice one that maintains technological progress while preserving moral integrity and public trust. Ultimately, AI should serve humanity as a tool for equitable development, not as an unregulated force detached from human conscience or accountability.